Credit/debt and human capital: Financialized neoliberalism and the production of subjectivity. (November 2019) - Bowsher, Josh
Adding to contemporary debates about the relationship between financialization and neoliberalism, this article investigates their entanglement at the level of subjectivity. Primarily, the article argues that financialization and neoliberalism are converging to produce a new form of subjectivity, post-profit homo œconomicus, an always indebted but credit-seeking enterprise. The value of this approach, the article demonstrates, is that it provides theoretical tools capable of grasping the differential production of subjectivity across the uneven and unequal striations of contemporary neoliberal society, from precarious workers of the gig economy to financial sector elites. The article examines two figures who have become central to public and academic debates about neoliberalism and financialization – the low-waged, precarious worker and the indebted student – to consider how neoliberal subjectivity is produced and distributed unevenly. It concludes that within these fragmentary socioeconomic positions are different instantiations of always indebted but credit-seeking human capital.